2018
DOI: 10.1210/js.2018-00131
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Androgen-Induced Cardiometabolic Effects in Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS), the most common endocrine disorder in women of reproductive age, is characterized by androgen excess and ovarian dysfunction and presents with increased cardiometabolic risk factors such as obesity, insulin resistance, and elevated blood pressure (BP). We previously reported that administration of dihydrotestosterone (DHT) to female rats elicits cardiometabolic derangements similar to those found in women with PCOS. In this study, we tested the hypothesis that the DHT-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Our PCOS model mimics several of the cardiometabolic features observed in women with PCOS, such as increases in BP and BMI, and decreases in insulin sensitivity. BP in this PCOS model is elevated by ~10 mmHg [ 25 , 29 , 30 ]. We also previously reported that blocking the RAS with an ACE inhibitor eliminated BP differences between treated PCOS and control rats [ 30 ], implicating activation of the RAS in the elevation of BP in our model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our PCOS model mimics several of the cardiometabolic features observed in women with PCOS, such as increases in BP and BMI, and decreases in insulin sensitivity. BP in this PCOS model is elevated by ~10 mmHg [ 25 , 29 , 30 ]. We also previously reported that blocking the RAS with an ACE inhibitor eliminated BP differences between treated PCOS and control rats [ 30 ], implicating activation of the RAS in the elevation of BP in our model.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the hyperandrogenemic rat model of PCOS recapitulates several cardiometabolic features observed in women with PCOS, including increased body mass index (BMI), IR, BP, hyperleptinemia, albuminuria, and activation of the intrarenal RAS [ 25 , 29 , 30 ]. In this study, we hypothesized that androgens upregulate the expression of renal SGLT2 and that SGLT2 inhibition ameliorates the cardiometabolic complications in an experimental model of PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…However, the slight elevation in insulin levels 2 months after removal of the letrozole pellet suggested that metabolism did not completely recover during this time frame. Given studies demonstrating that longterm exposure to androgens may result in permanent effects on metabolism [43], it would be interesting to further investigate how quickly metabolism normalizes after discontinuation of letrozole or androgen treatment and whether long-term androgen exposure can result in organizational effects on metabolism during adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the 16S rRNA gene sequencing employed in this study provided information about the taxonomic composition of the gut microbiome but not about functional changes. Given that a longer duration of androgen exposure may result in permanent effects on metabolism [43], it would be informative to employ metagenomic, transcriptomic or metabolomics analyses to understand whether exposure to excess androgens for a short or long duration can result in organizational or activational effects on gut microbial function.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, gonadectomy did not affect the expression or activity of ACE2 in male kidneys ( 72 ). We have previously reported that some of the renal actions of androgen excess in female rats persisted for months after androgen withdrawal ( 51 ); whether this is also the case in male mice is unknown. All these data highlight plenty of opportunities for further research to fully elucidate the role of sex steroids on ACE2 expression and activity regulation.…”
Section: The Raas Ace2 and Covid-19mentioning
confidence: 99%